Analisis Pengembangan Model Problem Project Based Learning Dalam Pembelajaran IPA - Fina Arfianti; Irdes Hidayana Siregar; Festiyed Festiyed; Yerimadesi Yerimadesi; Yuni Ahda; Heffi Alberida; Junil Adri (Unversitas Negeri Padang, 2025)
Science education in schools faces various challenges, such as the dominance of teacher-centered lecture methods, a lack of integration between theory and practice, and limited learning facilities. These issues hinder students from developing critical thinking, collaboration, and adaptability to modern demands. This study aims to develop a Problem-Project Based Learning (P2BL) model as a solution to address these challenges. The model integrates the strengths of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) to create contextual, practical learning experiences that encourage critical thinking among students. A Research and Development (R&D) approach with the ADDIE framework is employed to ensure the systematic development of the model. The P2BL model consists of five main components: syntax, reaction principles, social system, support system, and instructional as well as accompanying impacts. The syntax of this model includes stages such as problem definition, experimentation, planning, presentation, and evaluation, supported by multi-directional interactions between instructors and students, as well as collaboration among students. The research findings indicate that implementing the P2BL model enhances academic abilities, practical skills, and the development of attitudes such as teamwork, responsibility, and time management. With its relevance to the demands of the Industrial Revolution 4.0 era, the P2BL model offers a more interactive, effective, and adaptive learning alternative to improve the quality of Science education in schools.